PEMBELAJARAN PENDIDIKAN MULTIKEAKSARAAN DENGAN PENDEKATAN BAHASA IBU TEMA SOSIAL POLITIK DAN KEBANGSAAAN SUB TEMA: HAK ASASI MANUSIA, ORGANISASI DAN KELEMBAGAAN - Nunung Nurazizah (Direktorat Pendidikan Masyarakat dan Pendidikan Khusus, Direktorat Jenderal PAUD, Pendidikan Dasar, dan Pendidikan Menengah, 2019)
Social political theme with the sub-themes of human rights, organisation, and institution based on sample’s condition on high rate of divorce, domestic violence, and overlapping ownerships of lands. Study guide includes competency standard, fundamental competency, principal/learning material, learning activity, grading indicator, time allocation, grading system and source/substance/tool for learning that are design using local context and teaching material according to the problem issues and current potential which were written in two languages; Banjar and Indonesian. Teaching material, grading guide, multi-literacy education guide using the mother tongue approach, were structured for the completion of the learning means on multi-literacy education schooling activity in order for the learning participants to reach the competency standard of the multi-literacy education schooling accordingly to Ministry of Education and Culture’s Regulation No. 42 year 2015. The structuring of these teaching material, learning guide, and grading guide was using research and development methodology. The experiment of this research method was held at SPNF SKB Banjarbaru and PKBM Citra Mandurian of Tapin (as the treatment group) and SPNF SKB Tabalong (as the control group), from September to November 2018. The T-test on the product of multi-literacy education’s teaching material with the theme of social political theme and sub-themes of human rights, organisation, and institution, was obtained with the following calculation, Tapin’s knowledge : t-test =13.71 > ttable = 1.72. Banjarbaru’s knowledge : t-test =14.18 > ttable = 1.72; stated that Ho was disproven and H1 was accepted. The effect of the application of innovative teaching material was better than the conventional teaching material in shaping the learning participants’ multi-literacy knowledge in the province of South Borneo.